The relationship between illness perceptions, self-management, and quality of life in adult with type 2 diabetes mellitus - Yani Sofiani; Abdu Rahim Kamil; Fitrian Rayasari (Jurnal Keperawatan Padjadjaran, 2022)
Background: Few studies have examined the association between illness perception, self-management, and quality of life in adults with type 2 Diabetes Mellitus (DM), especially in resource-limited countries such as Indonesia. Purpose: This study aimed to evaluate the relationship between illness perception, self-management, and quality of life in adult with type 2 DM in Indonesia. Methods: The inclusion criteria were adult aged over 18 years old and diagnosed with type 2 DM. Convenience sampling was used in this study. A total of 351 patients with type 2 DM was recruited (response rate= 97.50%). This study used the following instrument: World Health Organization Quality of Life-BREF (WHOQOL-BREF), The Brief Illness Perception Questionnaire (B-IPQ), and Diabetes Self-Management Questionnaire (DSMQ). A Hierarchical regression models were constructed by using the score of overall QOL and those for each domain as the dependent variables. Results: The mean age was 54 (SD=8.14) years old and the mean time living with type 2 DM was 92 (SD=82.88) months. Higher illness perception score was significantly associated with lower physical health scores (Î² = -.395, SE = .096), psychological health (Î² = -.365, SE = .110), social relationships (Î² = -.363, SE = .138), and environment health (Î² = -.367, SE = .105). Conclusion: The findings indicated that poorer illness perceptions are associated with a lower quality of life. The findings establish a foundation for future interventions aimed at altering illness perceptions in order to promote self-care and improved quality of life in people with diabetes.